Lessons from contemporary trials of cardiovascular prevention and rehabilitation: A systematic review and meta-analysis. (1st April 2017) - van Halewijn, Gijs; Deckers, Jaap; Tay, Hung Yong; van Domburg, Ron; Kotseva, Kornelia; Wood, David
Abstract: Background: Meta-analyses of cardiac rehabilitation trials up to 2010 showed a significant reduction in all-cause mortality but many of these trials were conducted before the modern management of acute coronary syndromes. Methods: We undertook a meta-analysis of contemporary randomised controlled trials published in the period 2010 to 2015, including patients with other forms of atherosclerotic cardiovascular disease, to investigate the impact of cardiovascular prevention and rehabilitation on hard outcomes including survival. Results: 18 trials randomising 7691 patients to cardiovascular prevention and rehabilitation or usual care were selected. All-cause mortality was not reduced (RR 1.00, 95% CI 0.88 to 1.14), but cardiovascular mortality was by 58% (95% CI 0.21, 0.88). Myocardial infarction was also reduced by 30% (95% CI 0.54, 0.91) and cerebrovascular events by 60% (95% CI 0.22, 0.74). Comprehensive programmes managing six or more risk factors reduced all-cause mortality in a subgroup analysis (RR 0.63, 95% CI 0.43, 0.93) but those managing less did not. In the three programmes that prescribed and monitored cardioprotective medications for blood pressure and lipids all-cause mortality was also reduced (RR 0.35, 95% CI 0.18, 0.70). Conclusions: Comprehensive prevention and rehabilitation programmes managing six or more risk factors, and those prescribing and monitoring medications within programmes to lower blood pressure and lipids, continue to reduce all-cause mortality. In addition, these comprehensive programmes not only reduced cardiovascular mortality and myocardial infarction but also, for the first time, cerebrovascular events, and all these outcomes across a broader spectrum of patients with atherosclerotic disease. Highlights: Most prevention and rehabilitation programmes do not longer reduce mortality. Comprehensive prevention and rehabilitation programmes managing six or more risk factors continue to be effective in reducing all-cause mortality. Programmes that integrate prescription of cardioprotective medication also continue to reduce all-cause mortality. Myocardial infarction and, for the first time, cerebrovascular events are reduced.